The Case Against B. F. Skinner 45 years Later: An Encounter with N. Chomsky - Virués-Ortega, Javier (The Association for Behavior Analysis, Inc., 2006)
Chomsky's (1959) review of Verbal Behavior (Skinner, 1957) has been hailed as the most influential document in the history of psychology. Although many rejoinders to Chomsky's review have been published, their impact has been minimal. Moreover, Chomsky has not answered them in detail. To invite Chomsky to revisit a number of matters concerning the review, he was interviewed. The principal topics addressed by Chomsky were (a) historical factors associated with behaviorism after World War II; (b) circumstances surrounding the preparation of the review; (c) likely compatibility between formal and functional analyses of language; and (d) Chomsky's current point of view on aspects of the content of his review and on the evolution of behavior analysis.